Psychiatric and functional evaluation of professional athletes following anterior cruciate ligament reconstruction - SAKA, TOLGA; ÇELEBİ, MEHMET MESUT; BASKAK, BORA; SAKA, TOLGA; Devrimci Ozguven, Halise; ÜLKAR, BÜLENT; Atalar, Ebru (My University, 2015)
Objective: The aim of this study is to evaluate early phase depression and anxiety in the proffessional athletes who underwent anterior cruciate ligament (ACL) reconstruction and compare them with the functional improvement of knee.